Perovskite Light-Emitting Devices with Doped Hole Transporting Layer - Zhiwei Peng; Yuhan Gao; Guohua Xie (Molecules, 2021)
Perovskite quantum dots (PQDs) have drawn global attention in recent years and have been used in a range of semiconductor devices, especially for light-emitting diodes (LEDs). However, because of the nature of low-conductive ligands of PQDs and surface and bulk defects in the devices, charge injection and transport should be carefully managed in order to maximize the electroluminescent performances. In this study, we employed three p-dopants, i.e., 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ), 1,3,4,5,7,8-hexafluoro-11,11,12,12-tetracyanonaphtho-2,6-quinodimethane (F6-TCNNQ), and 11,11,12,12-tetracyanonaphtho-2,6-quinodimethane (TCNH14), respectively doped into the commonly used hole transporting layer (HTL) poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA). Compared with the devices with the neat PTAA, those with the doped PTAA as the HTLs achieved the improved electroluminescent performances. In particular, the device with the strong oxidant F4-TCNQ exhibited an improvement factor of 27% in the peak external quantum efficiency compared with the control device with the neat PTAA. The capacitance and transient electroluminescent measurements were carried out to identify the imperceptible interactions in the doped HTL and at the interface between the HTL and PQDs.